A produção do espaço rural no município de Ceará-Mirim - Montenegro, Maria Eliane (2004)
This research intended to study the process of production of the rural space in the municipal district of Little Ceará-Mirim, looking for to identify the transformations in him happened, above all in the last thirty years. Since the beginning of your historical formation, the area in study had as element modelador and transformer of the physiognomy of your territory the culture canavieira that printed in your economy and in your society marks of a powerful nobility. The sugar-cane is covered of a cyclical character facing acme phases and decadence, as the one that it happens at the present time. Simultaneously, the sphere rural cearimirinense is going by changes by the implantation of modern companies gone back to the papaya production destined to the internal market and more precisely to the external market. Of this context they also consist the supplying farms of this same product. In the group of the establishments in the rural landscape here analyzed, they still interfere the mixed farms, the ones that practice agriculture, the ones that were devoted to the livestock, as well as the farms and the ranches. Another innovation is the caprinocultura developed in modern molds, using the system voisin of pasture rodízio being constituted in a pioneering experience in Brazil. Of that reality they announce other elements, to example of the establishments, being configured as new forms of use of the soil. In the perspective of turning them productive, the challenge resides of overcoming the difficulties in them existent. The reality of the space in screen is replete of lacks in all the instances. It is inferred that the municipal district possesses an enormous potential, however the performance of the administrative components is seen as deficient. He becomes urgent that the municipal public power promotes changes, mainly in what it respects to the social area, with a better attendance to the rural communities, for them to act positively in the process of the development of this municipal district